Handbook of neuro-oncology neuroimaging - Newton, Herbert B. (Elsevier, Academic Press, an Imprint of Elsevier, 2022)
With treatment approaches and the field of neuro-oncology neuroimaging changing rapidly, this third edition of the Handbook of Neuro-Oncology Neuroimaging is very relevant to those in the field, providing a single-source, comprehensive, reference handbook of the most up-to-date clinical and technical information regarding the application of neuroimaging techniques to brain tumor and neuro-oncology patients. This new volume will have updates on all of the material from the second edition, and in addition features several new important chapters covering diverse topics such as imaging for the use of Laser Interstitial Thermal Therapy, advanced imaging techniques in radiation therapy, therapeutic treatment fields, response assessment in clinical trials, surgical planning of neoplastic disease of the spine, and more. Sections first overview neuro-oncological disorders before delving into the physics and basic science of neuroimaging and great focus on CT and MRI. The book then focuses on advances in the neuroimaging of brain tumors and neuroimaging of specific tumor types. There is also discussion of neuroimaging of other neuro-oncological syndromes. This book will serve as a resource of background information to neuroimaging researchers and basic scientists with an interest in brain tumors and neuro-oncology.